Peran Pondok Pesantren Modern Syekh Walid Thalib Saleh Dalam Pengembangan Dakwah di Desa Sungai Iliran Kecamatan Gaung Aanak Serka Kabupaten Indragiri Hilir - yous gunawan (STAI Hubbulwathan Duri, 2018)
Islamic boarding schools are Islamic educational institutions wherein they study religion. Like the Kalasik books, and other Shari'a books. The development of Islamic boarding schools has progressed which is not only dwelling on religious studies or classical books, but also teaching about modern general sciences that have been introduced including technology. In connection with this matter the Islamic boarding school is not only a forum for studying the knowledge of Islam but also as a vehicle for empowering the people. This is due to the progress of Islamic boarding schools from time to time. As we all know, the vision and mission of Islamic boarding schools is not a public secret, but the function and role of Islamic boarding schools is indeed a good empowerment of people from various fields such as; syi'ar religious (da'wah) study of books, history, cultural arts, natural sciences, astronomy, technology, sports, politics, economics, and so forth.